Composite sodium ferric phosphate positive electrode material and preparation method thereof
Through the two-step sintering method of water-soluble salt spray drying, the problem of tight particle connections in the production process of sodium ion battery positive electrode materials and easy destruction of the carbon layer on the surface of the material is solved, and the preparation of composite sodium ferrophosphate positive electrode materials with high purity and excellent electrochemical performance is achieved, which significantly improves the electrochemical performance and energy density.
Patent Information
- Application Number
- CN202411875702.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-18
AI Technical Summary
During the production process, existing sodium ion battery positive electrode materials have problems such as tight particle connection, easy damage to the carbon layer on the surface of the material, uneven particle distribution and difficult to regulate the morphology, resulting in a degradation of electrochemical performance.
The precursor was formed by spray-drying and low-temperature sintering by spray-drying and low-temperature sintering, followed by high-energy ball milling and high-temperature sintering to prepare a composite sodium iron phosphate positive electrode material with high purity and excellent electrochemical properties.
This method simplifies the process flow, avoids sand grinding steps, ensures the consistency of the quality of the material, and forms a small particle size and high crystalline composite sodium iron phosphate positive electrode material, which significantly improves the electrochemical performance and energy density.
Smart Images

Figure CN119841294A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a composite sodium iron phosphate positive electrode and a preparation method thereof. Background Art
[0002] Globally, the urgency of addressing climate change is becoming increasingly apparent. As one of the main areas of global greenhouse gas emissions, the automotive industry accounts for about 15% to 20% of global carbon emissions. With the increasing awareness of consumers about environmental protection and the support of government policies, the promotion of new energy vehicles has become an inevitable choice for industry transformation. Power batteries, as the "heart" of electric vehicles, play a vital role in this transformation process. However, my country faces severe challenges in the supply of lithium resources. The high dependence on lithium mineral resources makes my country subject to the production and application of power batteries. Therefore, the development of new battery technology, especially sodium-ion batteries, has become an important way to alleviate resource bottlenecks.
[0003] Sodium resources are extremely abundant in nature, mainly from seawater and ores. They are widely distributed and easy to obtain. Compared with the high cost and resource shortage of lithium batteries, sodium-ion batteries have become an important choice for future battery technology due to their abundance and low cost of raw materials. The extraction process of sodium is simple and environmentally friendly, especially the extraction of sodium carbonate, which has a stable supply and low price fluctuations, which makes sodium-ion batteries competitive in terms of economy.
[0004] At present, there are three main technical routes for the positive electrode materials of sodium-ion batteries, namely layered oxides, Prussian-type positive electrode materials and polyanion-type positive electrode materials. Layered oxides have a higher specific capacity (usually between 150 and 200 mAh / g), and their process is similar to that of ternary materials. However, during the production process, the crystal water generated in Prussian-type materials is difficult to remove, which affects the cycle performance and long-term stability of the materials. Polyanion-type materials have outstanding performance in stability, cycle performance and safety, and have become an important candidate material for future battery technology. Its specific capacity is usually between 100 and 150 mAh / g, but due to its good cycle performance and thermal stability, it is expected to have a wider application prospect in the market.
[0005] At present, the preparation method of commercial composite sodium iron phosphate (NFPP) positive electrode materials mainly adopts the solid phase method. Although this method is mature, there is a problem of tight connection of particles. In the subsequent air flow crushing process, the strong air flow will destroy the surface carbon layer of the material, resulting in a decrease in electrochemical performance. If air flow crushing is not used, the particles will not be effectively graded, further reducing the compaction density of the material. In addition, due to the traditional solid phase process, various raw materials are mixed by sand milling, and then sprayed and sintered at high temperature. The material particles prepared by this method are unevenly distributed, the morphology is difficult to control, and the raw materials cannot be mixed at the atomic level. In the subsequent sintering process, impurities of sodium iron phosphate and sodium iron pyrophosphate are easily generated, affecting the electrochemical properties such as capacity and rate. Summary of the invention
[0006] In view of the shortcomings of the existing preparation process, the purpose of the present invention is to provide a composite sodium iron phosphate positive electrode material with high production efficiency, high product phase purity and excellent electrochemical performance and a preparation method thereof.
[0007] The preparation method of the composite sodium iron phosphate positive electrode material (NFPP) provided by the present invention comprises the following specific steps:
[0008] (1) dissolving a sodium source, an iron source, a phosphorus source, and a first carbon source in a required proportion to prepare a solution;
[0009] (2) spray drying the solution in step (1) to obtain a spray material;
[0010] (3) sintering the sprayed material at low temperature in an inert atmosphere to obtain a first precursor;
[0011] (4) mixing the first precursor and the second carbon source uniformly, and crushing them by high-energy ball milling to obtain the second precursor;
[0012] (5) sintering the second precursor at high temperature under an inert atmosphere to obtain a composite sodium iron phosphate positive electrode material;
[0013] Preferably, the sodium source in step (1) is selected from one or more of sodium chloride, sodium carbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium carbonate.
[0014] Preferably, the iron source in step (1) is selected from one or more of ferric chloride, ferric sulfate and ferric nitrate.
[0015] Preferably, the phosphorus source in step (1) is selected from one or more of phosphoric acid, ammonium phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.
[0016] Preferably, the first carbon source in step (1) is selected from one or more of glucose, sucrose, polyethylene glycol, and citric acid, and the mass proportion of the first carbon source in the sum of all raw materials in step (1) is 10-25% (preferably 12-20%). The main function of the first carbon source is to ensure that the trivalent iron in the raw material is reduced to divalent iron. If the amount of the first carbon source added is too little, the trivalent iron reduction is incomplete, and the final material contains more impurities, which affects the electrochemical performance. If the amount of the first carbon source added is too much, the amount of the carbon source added in the second step is too little, and it will gather on the spherical surface of the spray material during the spraying process, and the internal space cannot be evenly coated.
[0017] Preferably, the molar ratio of Na:Fe:P provided by the sodium source, iron source and phosphorus source in step (1) is 4:(2.8-3.1):4. If the iron content is too little, the material will transform into a thermodynamically more stable sodium iron pyrophosphate phase, resulting in a decrease in electrochemical performance; if the iron content is too much, the material will transform into a thermodynamically more stable sodium iron phosphate phase, which is an electrochemically inactive phase, resulting in a deterioration in electrochemical performance.
[0018] Preferably, the spray drying in step (2) has an inlet air temperature of 180-240° C., an outlet air temperature of 120-140° C., and an atomization pressure of 0.2-0.3 MPa. The inlet air temperature and atomization pressure will affect the morphology and particle size of the material.
[0019] Preferably, the low-temperature sintering protective atmosphere in step (3) is nitrogen or argon, the sintering temperature is 250-350° C., and the sintering time is 8-12 hours.
[0020] Preferably, the second carbon source in step (4) is selected from one or more of glucose, sucrose, polyethylene glycol, citric acid, melamine, graphene, and carbon nanotubes; the mass of the second carbon source in the second precursor accounts for 0.5-5% (preferably 1-4%). The content of the second carbon source must be strictly controlled. If the content is too little, the material cannot be coated evenly and effectively. If the content is too much, the carbon coating layer will be too thick, affecting the sodium ion deintercalation rate and causing the deterioration of the electrochemical performance.
[0021] Preferably, the low-temperature sintering protective atmosphere in step (5) is nitrogen or argon, the sintering temperature is 500-600°C, and the sintering time is 8-12 hours. The sintering conditions should be strictly controlled during the sintering process. If the sintering temperature of the material is too low or the holding time is too short, the material crystallization phase is incomplete; if the sintering temperature is too high or the holding time is too long, non-electrochemically active impurities will be generated, further affecting the electrochemical performance.
[0022] Compared with the existing preparation process, the beneficial effects of the present invention are:
[0023] The water-soluble salt spray drying two-step sintering preparation process provided by the present invention is simple and easy to operate, eliminating the complex and energy-consuming sand milling step, and the uniformity of the water-soluble salt effectively avoids the segregation of the raw materials during the spraying process, ensuring the quality consistency of the material. The finally synthesized NFPP positive electrode material presents a hollow structure, is easy to break, can improve efficiency in subsequent processing, has good crystallinity, small particle size, excellent electrochemical performance, and can be effectively graded with commercial materials to improve compaction density and energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 This is the XRD spectrum of the composite sodium iron phosphate provided in Example 1.
[0026] Figure 2 This is the 0.1C first cycle charge and discharge curve of the composite sodium iron phosphate provided in Example 1.
[0027] Figure 3 This is the cycle performance diagram of the composite sodium iron phosphate provided in Example 1.
[0028] Figure 4 This is the rate performance diagram of the composite sodium iron phosphate provided in Example 1. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Example 1, a method for preparing a composite sodium iron phosphate positive electrode material, the specific steps are:
[0031] (1) Dissolve 48.48 g of anhydrous sodium dihydrogen phosphate, 118.75 g of ferric nitrate nonahydrate, and 33.45 g of citric acid in 600 ml of ultrapure water and stir to dissolve.
[0032] (2) The solution in step (1) is spray-dried at an air inlet temperature of 240° C. and an air outlet temperature of 130° C. to obtain a spray material.
[0033] (3) The spray material in (2) was sintered in an Ar atmosphere at a heating rate of 5°C / min, a sintering temperature of 300°C, and a holding time of 5h to obtain a first precursor.
[0034] (4) 10 g of the first precursor and 0.5 g of citric acid were mixed evenly, and the mixture was crushed by high-energy ball milling at 700 rpm to obtain the second precursor.
[0035] (5) The second precursor is sintered in an Ar atmosphere with a heating rate of 5°C / min, a sintering temperature of 550°C, and a holding time of 8 h to obtain a composite sodium iron phosphate positive electrode material.
[0036] Example 2, a method for preparing a composite sodium iron phosphate positive electrode material, the specific steps are:
[0037] (1) 48.48 g of anhydrous sodium dihydrogen phosphate, 114.26 g of ferric nitrate nonahydrate, and 33.45 g of citric acid were dissolved in 600 ml of ultrapure water and stirred to dissolve.
[0038] (2) The solution in step (1) is spray-dried at an air inlet temperature of 240° C. and an air outlet temperature of 130° C. to obtain a spray material.
[0039] (3) The spray material in (2) was sintered in an Ar atmosphere at a heating rate of 5°C / min, a sintering temperature of 300°C, and a holding time of 5h to obtain a first precursor.
[0040] (4) 10 g of the first precursor and 0.5 g of citric acid were mixed evenly, and the mixture was crushed by high-energy ball milling at 700 rpm to obtain the second precursor.
[0041] (5) The second precursor is sintered in an Ar atmosphere with a heating rate of 5°C / min, a sintering temperature of 550°C, and a holding time of 8 h to obtain a composite sodium iron phosphate positive electrode material.
[0042] Example 3, a method for preparing a composite sodium iron phosphate positive electrode material, the specific steps are:
[0043] (1) Dissolve 48.48 g of anhydrous sodium dihydrogen phosphate, 122.42 g of ferric nitrate nonahydrate, and 33.45 g of citric acid in 600 ml of ultrapure water and stir to dissolve.
[0044] (2) The solution in step (1) is spray-dried at an air inlet temperature of 240° C. and an air outlet temperature of 130° C. to obtain a spray material.
[0045] (3) The spray material in (2) was sintered in an Ar atmosphere at a heating rate of 5°C / min, a sintering temperature of 300°C, and a holding time of 5h to obtain a first precursor.
[0046] (4) 10 g of the first precursor and 0.5 g of citric acid were mixed evenly, and the mixture was crushed by high-energy ball milling at 700 rpm to obtain the second precursor.
[0047] (5) The second precursor is sintered in an Ar atmosphere with a heating rate of 5°C / min, a sintering temperature of 550°C, and a holding time of 8 h to obtain a composite sodium iron phosphate positive electrode material.
[0048] Example 4, a method for preparing a composite sodium iron phosphate positive electrode material, the specific steps are:
[0049] (1) Dissolve 48.48 g of anhydrous sodium dihydrogen phosphate, 122.42 g of ferric nitrate nonahydrate, and 33.45 g of citric acid in 600 ml of ultrapure water and stir to dissolve.
[0050] (2) The solution in step (1) is spray-dried at an air inlet temperature of 240° C. and an air outlet temperature of 130° C. to obtain a spray material.
[0051] (3) The spray material in (2) was sintered in an Ar atmosphere at a heating rate of 5°C / min, a sintering temperature of 300°C, and a holding time of 5h to obtain a first precursor.
[0052] (4) 10 g of the first precursor and 0.5 g of citric acid were mixed evenly, and the mixture was crushed by high-energy ball milling at 700 rpm to obtain the second precursor.
[0053] (5) The second precursor is sintered in an Ar atmosphere with a heating rate of 5°C / min, a sintering temperature of 500°C, and a holding time of 8 h to obtain a composite sodium iron phosphate positive electrode material.
[0054] Example 5, a method for preparing a composite sodium iron phosphate positive electrode material, the specific steps are:
[0055] (1) Dissolve 48.48 g of anhydrous sodium dihydrogen phosphate, 122.42 g of ferric nitrate nonahydrate, and 33.45 g of citric acid in 600 ml of ultrapure water and stir to dissolve.
[0056] (2) The solution in step (1) is spray-dried at an air inlet temperature of 240° C. and an air outlet temperature of 130° C. to obtain a spray material.
[0057] (3) The spray material in (2) was sintered in an Ar atmosphere at a heating rate of 5°C / min, a sintering temperature of 300°C, and a holding time of 5 h to obtain a first precursor.
[0058] (4) 10 g of the first precursor and 0.5 g of melamine were mixed evenly, and the mixture was crushed by high-energy ball milling at 700 rpm to obtain the second precursor.
[0059] (5) The second precursor is sintered in an Ar atmosphere with a heating rate of 5°C / min, a sintering temperature of 550°C, and a holding time of 8 h to obtain a composite sodium iron phosphate positive electrode material.
[0060] Electrochemical performance test: The composite sodium iron phosphate positive electrode material obtained in Examples 1 to 6 was mixed with PVDF and SuperP in a mass ratio of 90:5:5, homogenized with NMP, and the dispersed slurry was applied on aluminum foil and placed in an oven at 80°C under vacuum for 12 h. After rolling and cutting, a positive electrode sheet with a diameter of 12 mm was obtained. Button cells were made in an argon glove box with a water oxygen value of less than 0.1 ppm. The sodium sheet, blotting paper, diaphragm, and positive electrode sheet were stacked in order, 70 μL of electrolyte (1 mol / L NaClO4 EC+DEC+EMC solution) was injected, and the seal was sealed with a sealer. After standing for 12 h, the test was performed. The voltage range was 2.0 V to 4.0 V, and the nominal specific capacity was 129 mAh / g. The test results are shown in Table 1:
[0061] Table 1 Electrochemical performance test results
[0062]
[0063] Before the electrochemical performance test, each button cell to be tested needs to be formed, specifically: let it stand for 12 hours, charge it at a constant current of 0.1 C to 4.0 V, then charge it at a constant voltage of 4.0 V to a current rate less than 0.05 C, let it stand for 5 minutes, and then discharge it at a constant current to 2.0 V. This cycle is repeated three times to complete the formation process.
[0064] The batteries of Examples 1 to 6 were subjected to rate tests, and the test conditions were as follows: the prepared batteries were placed in a constant temperature oven at 25°C, left to stand for 2 h, charged to 4.0 V at a constant current rate of 1 C, then charged to a current rate of less than 0.05C at a constant voltage of 4.0 V, left to stand for 5 min, and then discharged to 2.0 V at a constant current rate of 1 C, and this cycle was repeated for 5 cycles, and then this process was repeated for 5 cycles at 2C and 5C respectively to complete the rate test process.
[0065] It can be seen from Table 1 that the composite sodium iron phosphate provided by the embodiment of the present invention exhibits excellent rate performance.
[0066] The composite sodium iron phosphate prepared in Example 1 is representative, and its XRD spectrum is shown in Figure 1 As shown; 0.1C first cycle charge and discharge curve is shown Figure 2 As shown; the cycle performance will Figure 3 As shown; rate performance see Figure 4As shown. The specific capacity of the composite sodium iron phosphate at 0.1C reached 104.86 mAh / g, and the ratio of 5C / 0.1C also reached 91.61%, with the best rate performance. Figure 3 It can be clearly seen from the cycle diagram that the capacity does not decay after a long cycle, showing excellent cycle performance.
[0067] In summary, the present invention provides a method for preparing composite sodium iron phosphate, which uses a water-soluble salt spray drying method to eliminate the complex and energy-consuming sand milling step. The uniformity of the water-soluble salt effectively avoids the segregation of elements in the spraying process of the traditional solid-phase sand milling slurry, ensuring the consistency of the material. The preparation method is simple and convenient, has low requirements on equipment, and can accurately synthesize a small-particle-size, highly crystalline composite sodium iron phosphate positive electrode material. Its unique morphology and particle size enable the assembled battery to exhibit excellent electrochemical performance, which has great commercial value.
[0068] The above embodiments describe the basic principles, main features and advantages of the present invention, which are merely examples for the purpose of clarifying the description, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing a composite sodium iron phosphate positive electrode material, characterized in that: The specific steps are: (1) dissolving a sodium source, an iron source, a phosphorus source, and a first carbon source in a required proportion to prepare a solution; (2) spray drying the solution in step (1) to obtain a spray material; (3) sintering the sprayed material at low temperature under an inert atmosphere to obtain a first precursor; (4) mixing the first precursor and the second carbon source uniformly, and crushing them by high-energy ball milling to obtain the second precursor; (5) The second precursor is sintered at high temperature in an inert atmosphere to obtain a composite sodium iron phosphate positive electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1): The sodium source is selected from sodium chloride, sodium carbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium carbonate; The iron source is selected from ferric chloride, ferric sulfate, and ferric nitrate; The phosphorus source is selected from phosphoric acid, ammonium phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate; The first carbon source is selected from glucose, sucrose, polyethylene glycol, and citric acid.
3. The preparation method according to claim 2, characterized in that: In step (1): The first carbon source accounts for 10-25% of the total mass of all raw materials; The molar ratio of Na:Fe:P provided by the sodium source, iron source and phosphorus source is 4:(2.8-3.1):
4.
4. The preparation method according to claim 3, characterized in that: The spray drying in step (2) has an inlet air temperature of 180-240°C, an outlet air temperature of 120-140°C, and an atomization pressure of 0.2-0.3 MPa.
5. The preparation method according to claim 4, characterized in that: The low-temperature sintering protective atmosphere in step (3) is nitrogen or argon, the sintering temperature is 250-350°C, and the sintering time is 8-12 hours.
6. The preparation method according to claim 5, characterized in that: In step (4), the second carbon source is selected from glucose, sucrose, polyethylene glycol, citric acid, melamine, graphene, and carbon nanotubes; and the mass proportion of the second carbon source in the second precursor is 0.5-5%.
7. The preparation method according to claim 6, characterized in that: The low-temperature sintering protective atmosphere in step (5) is nitrogen or argon, the sintering temperature is 500-600°C, and the sintering time is 8-12 h.
8. A composite sodium iron phosphate positive electrode material obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Cited By
High-compaction ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN120348921A
Modified composite sodium ferric phosphate positive electrode material and preparation method and application thereof
CN120646797A